2017
DOI: 10.1186/s12985-017-0787-4
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antibodies protect offspring from severe influenza infection and do not lead to detectable interference with subsequent offspring immunization

Abstract: BackgroundVarious studies have shown that infants under the age of 6 months are especially vulnerable for complications due to influenza. Currently there are no vaccines licensed for use in this age group. Vaccination of pregnant women during the last trimester, recommended by the WHO as protective measure for this vulnerable female population, may provide protection of newborns at this early age. Although it has been observed that maternal vaccination can passively transfer protection, maternal antibodies cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Regarding the natural anti-carbohydrate repertoire, our results show that in early weaned mice (3 weeks) the repertoire of natural anti-glycan antibodies is quite limited, meaning that the immune system of young animals is at a very early stage of development. These antibodies detected at month-1 could be the result of passive immunization ( 47 ) through the placenta during the pregnancy (IgG) or via mother's milk (most of them are IgA), to protect the offspring from potential threats like bacterial infections during the first stage of life. The same general analysis applies to microbiota diversity; lactating mice don't need complex and diverse microbiota when milk is the primary dietary intake during the first month of life.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the natural anti-carbohydrate repertoire, our results show that in early weaned mice (3 weeks) the repertoire of natural anti-glycan antibodies is quite limited, meaning that the immune system of young animals is at a very early stage of development. These antibodies detected at month-1 could be the result of passive immunization ( 47 ) through the placenta during the pregnancy (IgG) or via mother's milk (most of them are IgA), to protect the offspring from potential threats like bacterial infections during the first stage of life. The same general analysis applies to microbiota diversity; lactating mice don't need complex and diverse microbiota when milk is the primary dietary intake during the first month of life.…”
Section: Discussionmentioning
confidence: 99%
“…Infants between 6 and 12 months experienced relatively high rates of hospitalization in an RCT comparing inactivated vaccine and LAIV and consequently, LAIV has only been recommended in infants greater than 12 months of age ( 76 ). There is currently no available influenza vaccine for infants younger than 6 months, however, maternal immunization provides passive protection ( 77 ) and in a murine model, there was no evidence of maternal interference ( 78 ).…”
Section: Current Research On Early Life Immunizationmentioning
confidence: 99%
“…It is speculated that the function of ACE2 protein in adults is stronger than that of children; therefore, SARS-CoV-2 is more infectious in adults [99] . Other studies reported that maternal antibodies can protect infants and young children from microbes immunized by the mother, so children are completely new to all microbes that have not been immunized by the mother [100] . New memory T and B cell pools can be established in the immune system of infants and young children, and reinfection of common pathogens can also be controlled.…”
Section: Sars-cov-2 and Cardiovascular Involvementmentioning
confidence: 99%